Tight integration of Artificial Intelligence in Game Development Tools - Angilica, Denise; Greco, Gianluigi; Ianni, Giovambattista (Università della Calabria, 2020)
In this thesis we aim to narrow some of the gaps that prevent the adoption of declarative tools within highly dynamically changing environments, with a particular focus to the context of game development. Integrating reasoning modules, based on declarative speci cations, within the commercial game development life-cycle, poses a number of unsolved challenges, each with nonobvious solution. It is necessary to cope with strict time performance requirements; the duality between procedural code and declarative speci cations prevents easy integration; the concurrent execution of reasoning tasks and game updates requires proper information passing strategies between the two involved sides. In this context, we propose a framework that can be deployed within the well-known Unity game development engine. The so-called ThinkEngine framework allows to embed reasoning modules, based on knowledge representation techniques, within the game logic. ThinkEngine respects the Unity development philosophy, and is properly integrated both at design-time and at run-time. A use case is reported about, showing the potential of the proposed infrastructure.
Dottorato di Ricerca in Matematica e Informatica, XXXI ciclo
Keywords: ASP-Unity; Videogame; Stream reasoning; Tetris